The Relationship between Coffee and Tea Consumption with the Incidence of Gastroesophageal Reflux Disease (GERD) among Students at Muhammadiyah University - Nuralam, Muhammad Fathan; Setiyadi, Noor Alis (Universitas Nahdlatul Ulama Surabaya, 2025)
Gastroesophageal Reflux Disease (GERD) is a condition where stomach acid rises back into the esophagus, which can negatively impact the quality of life, particularly among students who have coffee and tea consumption habits. This study aimed to analyze whether there is a relationship between coffee and tea consumption habits and the incidence of GERD among students at Muhammadiyah University. The study employed a case-control design involving 100 respondents (20 cases and 80 controls). Data were collected using the GERD-Q questionnaire and a validated and reliable questionnaire on coffee and tea consumption habits, which were then, analyzed using the Chi-Square test. The results showed that coffee consumption habits and coffee consumption duration of ≥4 years were significantly associated with the incidence of GERD among students. In contrast, tea consumption habits and tea consumption duration of ≥4 years were not significantly associated with GERD, although students who regularly consumed tea had a higher risk of developing GERD compared to those who did not regularly consume tea. Students are advised to regulate their coffee and tea consumption habits to reduce the risk of GERD. Keywords: Caffeine, coffee consumption, GERD, students, tea consumption